2020
DOI: 10.1007/s00464-020-07542-3
|View full text |Cite
|
Sign up to set email alerts
|

Could fluorescence-guided surgery be an efficient and sustainable option? A SICE (Italian Society of Endoscopic Surgery) health technology assessment summary

Abstract: Background Indocyanine green fluorescence vision is an upcoming technology in surgery. It can be used in three ways: angiographic and biliary tree visualization and lymphatic spreading studies. The present paper shows the most outstanding results from an health technology assessment study design, conducted on fluorescence-guided compared with standard vision surgery. Methods A health technology assessment approach was implemented to investigate the economic, social, ethical, and organizational implications rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 71 publications
(86 reference statements)
1
7
0
Order By: Relevance
“…In general, surgical procedures guided by uorescence with ICG have demonstrated advantages in the patient's length of stay (LOS) in hospital, especially for colorectal surgery, with a reduction in anastomotic leakage rates and redo anastomosis, at the expense of a slight increase in operating time. This study as well as multiple studies completed to date, con rms that this imaging technology is safe, effective and sustainable [19].…”
Section: Resultssupporting
confidence: 58%
“…In general, surgical procedures guided by uorescence with ICG have demonstrated advantages in the patient's length of stay (LOS) in hospital, especially for colorectal surgery, with a reduction in anastomotic leakage rates and redo anastomosis, at the expense of a slight increase in operating time. This study as well as multiple studies completed to date, con rms that this imaging technology is safe, effective and sustainable [19].…”
Section: Resultssupporting
confidence: 58%
“…Application of the EUnetHTA Core Model in HTA research is not new. [44][45][46] Although technologies, jurisdictions, and purposes differ among studies, the use of similar terminology and definitions increases transferability and dissemination of HTA practices. In a previous research, Radaelli et al 45 described that issues identified based on the EUnetHTA workflow resembled questions that needed to be addressed in the assessment.…”
Section: Discussionmentioning
confidence: 99%
“…It is safe since adverse events are reported in less than 1 in 40.000 patients and mostly including hypersensitivity reactions ( 25 , 26 ). It is used in surgery for various purposes: evaluation of the anastomotic blood supply, visualization of the biliary tract during cholecystectomy, identification of the sentinel lymph node in breast cancer, melanoma and gastric carcinoma ( 27 32 ), but its use in bariatric surgery is still debated ( 22 24 ).…”
Section: Introductionmentioning
confidence: 99%